PENGUATAN LITERASI FINANSIAL SANTRI MELALUI PELATIHAN PENGELOLAAN KEUANGAN PRIBADI BERBASIS NILAI ISLAM DI PONDOK PESANTREN DAARUL AZMI - Irfan Rizka Akbar; Muhamad Faruq Setiadi; Nur Avni Indahsari; Rahma Fadhila (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
The low level of financial literacy among Islamic boarding school students (santri) is an issue that requires serious attention. Students often struggle to manage their allowances, distinguish needs from wants, prepare simple budgets, and develop consistent saving habits. This Community Service activity (PKM) aims to improve the financial literacy of santri at Daarul Azmi Islamic Boarding School, Kp. Rawalembang, Cibinong Village, Gunung Sindur District, Bogor Regency, through personal financial management training integrated wirh Islamic values. The implementation methods included financial literacy counseling, simple budget preparation training, allowance management simulations, interactive discussions, educational games, and practical financial mentorinng. This activity involved 15 students from the Management Study Program of Universitas Pamulang under the supervision of a supervising lecturer and was held on March 12, 2026. The result showed significant improvements in the students’ understanding of financial literacy concepts, budgeting skills, ability to distinguish needs from wants, saving awareness, and confidence in making financial decisions. This program also successfully instilled Islamic Financial principles such as amanah (trustworthiness), qana’ah (contentment), and avoiding israf (extravagance). These findings affirm that integrating Islamic values in financial education significantly enhances the effectiveness of financial literacy training in the pesantren environment. Sustained mentoring programs are needed to maintain and optimize students’ financial management capabilities in the long term.